2018
DOI: 10.4236/jilsa.2018.101001
|View full text |Cite
|
Sign up to set email alerts
|

BioBroker: Knowledge Discovery Framework for Heterogeneous Biomedical Ontologies and Data

Abstract: A large number of ontologies have been introduced by the biomedical community in recent years. Knowledge discovery for entity identification from ontology has become an important research area, and it is always interesting to discovery how associations are established to connect concepts in a single ontology or across multiple ontologies. However, due to the exponential growth of biomedical big data and their complicated associations, it becomes very challenging to detect key associations among entities in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In this study, we used a heuristic way to determine silhouette score and the number of clusters for making clear separations over the biomedical entities. In the future, we sought to use our previously developed hierarchical clustering optimization algorithms to make dynamic balance between the optimal silhouette score and suitable cluster density [42][43][44]. Moreover, after checking top similar entities for five selected coronavirus infectious diseases, we observed that applying clustering over the network embeddings could detect both explicit and implicit associations.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…In this study, we used a heuristic way to determine silhouette score and the number of clusters for making clear separations over the biomedical entities. In the future, we sought to use our previously developed hierarchical clustering optimization algorithms to make dynamic balance between the optimal silhouette score and suitable cluster density [42][43][44]. Moreover, after checking top similar entities for five selected coronavirus infectious diseases, we observed that applying clustering over the network embeddings could detect both explicit and implicit associations.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…e SW technologies (i.e., RDF, RDFs, OWL, and SPARQL) are based on W3C standards, which are aimed to materialize the SW initiatives by codifying formal and explicit definitions of the basic concepts and their relationships in a domain of interest in an easily understandable manner for the computer-based agents [7]. e SW technologies provide opportunities to deal with data heterogeneity, which could hinder the organization, interlinking, and sharing of datasets generated by different providers belonging to the same context [12,13]. e Linked Data (LD) represents a set of best practices methods to take advantage of the SW by using SW technologies for publishing structured data as resources on the Web and interlinking them semantically with related datasets on the Web [14].…”
Section: Background Sw and Lodmentioning
confidence: 99%
“…With the growing interest in semantic resources, several recent approaches have been proposed for semantically analysing user queries and matching them at a semantics-based level to their related documents. However, these approaches either use a single semantic resource such as Lu et al (2015), , Han et al (2016), Selmi et al (2018), Boiński et al (2018) and Royo et al (2005) or multiple heterogeneous semantic resources such as Maree et al (2016), Vigneshwari and Aramudhan (2015), Shen and Lee (2018), Kmail et al (2015), Zhu and Iglesias (2018), Goldfarb and Le Franc (2017) and Wimalasuriya and Dou (2009). For instance, the system proposed in Royo et al (2005) maps query keywords to their corresponding synsets in WordNet ontology.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, there has been attempts to exploit multiple semantic resources in specialised domains such as the recruitment domain (Kmail et al, 2015), biomedical information retrieval domain (Shen and Lee, 2018) and the information extraction domain (Wimalasuriya and Dou, 2009). For instance, in Wimalasuriya and Dou (2009), the authors demonstrated through experimental results that by using multiple ontologies the quality of the system's precision can be improved.…”
Section: Related Workmentioning
confidence: 99%